Effective staining method with iodine for leukoplakia and lesions surrounding squamous cell carcinomas of the tongue assessed by colorimetric analysis - Keiko Maeda; Masashi Yamashiro; Yasuyuki Michi; Tetsuo Suzuki; Yoshio Ohyama; Norihiko Okada; Teruo Amagasa (Journal of Medical and Dental Sciences, 2009)
To determine whether staining with iodine solution provides an efficient criterion for determining the area of resection for the lesions surrounding squamous cell carcinoma (SCC) and leukoplakia of the tongue, we determined the optimum density of iodine solution and staining procedure and analyzed the color of lightly stained lesions (LSLs) in relation to the histopathologic findings. Sixty-five patients with SCC or leukoplakia of the tongue were divided into two groups: lesions stained with 3% Lugol solution and restained with either 5% Lugol solution (n=38) or 10% iodine glycerin (n=27). Among the lesions stained with 5% Lugol solution, significant differences were found in all color values. Color difference values (ΔE*ab) using 3% and 5% Lugol solutions were significantly different between epithelial hyperplasia/mild epithelial dysplasia and moderate to severe dysplasia (P < 0.05). According to the evaluations of five clinicians in 46 LSLs, a distinctive boundary was most often obtained using 5% Lugol solution. These results suggest that the most effective method for obtaining a clear boundary and distinguishing moderate to severe dysplasia from mild or no epithelial dysplasia according to the measured color value was to stain with 3% followed by 5% Lugol solution.